CLINICAL COURSE AND TREATMENT FEATURES OF ORAL LEPTOTRICHOSIS - Skrypnikova, T.P.; Skrypnykov, P.M.; Khavalkina, L.M.; Tkachenko, I.M.; Khmil, T.A.; Pysarenko, O.A.; Dihtiar, N.I. (World of Medicine and Biology, 2023)
The oral microflora is highly diverse and includes actinomycetes, fungi, protozoa, spirochetes, rickettsia and viruses. Among them, Candida albicans has the highest pathogenicity, particularly associated with causing mycoses. Leptotrichia, similar to the fungi residing in the oral cavity, shares morphological characteristics, cell wall structure and antigenic properties. Morphologically, cell wall structure and antigenic composition are considered part of the opportunistic flora of the oral cavity and obligate anaerobes. In this regard, some authors hypothesize that abundant growth of Leptotrichia does not necessarily indicate pathology. Others consider eptotrichosis as a disease akin to opportunistic mycoses. However, there is a third perspective, where some authors classify leptotrichosis as an HIV-associated disease. Such divergence in opinions prompts a critical evaluation and leads to conclusions about the necessity of treating leptotrichosis. Moreover, in recent years, the number of individuals diagnosed with leptotrichosis has significantly increased. Therefore, leptotrichosis appears to be a distinct response of the oral mucosa to Leptotrichia infection, the activation and proliferation of which occur under specific conditions. The treatment was carried out according to the commonly accepted protocol, supplemented with the use of the drug to expedite the recovery process. The diagnosis was established based on clinical, anamnestic and laboratory study methods. The illness is chronic, with the possibility of observation over many months and years. Treatment is prolonged and requires persistence. The treatment plan may undergo changes. Clinical and laboratory indices serve as criteria for recovery.
Keywords: candidiasis; leptotrichosis; treatment; oral mucosa